Selenium-Cultured Potamogeton maackianus in the Diet Can Alleviate Oxidative Stress and Immune Suppression in Chinese Mitten Crab (Eriocheir sinensis) Under Copper Exposure - Qiang, Jun; Duan, Xue-Jun; Zhu, Chuan-Kun; He, Jie; Bao, Jin-Wen; Tao, Yi-Fan; Zhu, Hao-Jun; Xu, Pao (Frontiers in Physiology, 2020)
Selenium (Se) is an essential trace element for aquatic animals. The aquatic plant Potamogeton maackianus is an important natural food of Chinese mitten crab (Eriocheir sinensis). The aim of this study was to determine whether the antioxidant and immune responses of Chinese mitten crab are affected by including Se-cultured P. maackianus in the diet. Three groups of P. maackianus were cultured at levels of 0.02 mg/kg Se, 8.83 mg/kg Se, and 16.92 mg/kg Se, and the plants in these groups were used in experimental diets fed to crabs (dietary Se content of 0.05 mg/kg, 0.43 mg/kg, and 0.82 mg/kg, respectively). Compared with crabs in the 0.05 mg/kg group, those in the 0.82 mg/kg group showed significantly increased specific growth rate, protease and lipase activities, triglyceride and cholesterol contents, and Se content in the hepatopancreas and muscle (P<0.05); increased activities of glutathione peroxidase, glutathione reductase, and catalase in the antioxidant system; increased transcript levels of MT (encoding metallothionein); and decreased malondialdehyde content (P<0.05). At the end of the rearing experiment, the crabs in the different groups were exposed to copper (Cu2+) stress for 96 h. All the juvenile crabs in the 0.43 and 0.82 mg/kg groups survived 96 h of Cu2+ stress. Crabs in the 0.82 mg/kg group showed enhanced antioxidant responses under Cu2+ stress, increased transcript levels of MT and LYZ, and increased resistance. Therefore, supplementation of the diet of Chinese mitten crab with increased levels of Se-cultured P. maackianus can reduce oxidative stress under Cu2+ exposure, activate the immune response, and benefit growth.